The prototype of the Greenhouse Smart Control and Monitoring System in Hydroponic Plants - Arif Supriyanto; Fathurrahmani Fathurrahmani (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2019)
This research helps the farmers to do the humidification control and monitor the condition of hydroponic plants in greenhouses in real-time. When it comes to monitor the hydroponic plants in greenhouses, the farmers usually experience difficulties because they still do it manually. Activities such as checking the temperature, air humidity, and also water quality in hydroponic plants by coming directly to the greenhouse are still ineffective. Therefore this research aims to make a smart greenhouse prototype for hydroponic plants. Smart greenhouse hardware was built based on the Arduino microcontroller, DHT11 sensor, pH sensor, TDS, DS18b20 temperature, ultrasonic, and esp8266 wifi module. The monitoring system features information on water quality from hydroponic plants and the ability to record farming activities from planting preparation to web-based harvesting. The test results of smart greenhouse monitoring system can display the hydroponic plant conditions and able to do the humidification control with an upper limit of 35 degrees celsius because plant can survive with disease under 35 degrees celsius, with small average offset for the sensor, and an average offset of 1.49 from TDS sensors, with temperature of 0.50 and pH of 0.34. Keywords: Greenhouse, NFT hydroponics, Humidification, Monitoring System, Arduino